LIBRARY AND HALAL KNOWLEDGE MANAGEMENT: AN ISLAMIC INFORMATION SCIENCE PERSPECTIVE - Wicaksono, Moch. Fikriansyah (Faculty of Islamic Economic and Business - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract: The development of the halal industry has become a global phenomenon that covers various sectors, including food, pharmaceuticals, cosmetics, and finance. However, limited access to valid halal information is still a major challenge for consumers, business actors, and researchers. This article aims to explore the role of libraries in halal knowledge management and how libraries can become credible information centers in supporting the halal industry. The method used in this study is a literature review that refers to various academic sources related to halal and information management. The results of the study show that libraries have a strategic role in providing access to halal literature, developing digital repository systems, and integrating information technology such as blockchain and artificial intelligence (AI) to improve the validation and classification of halal information. In addition, collaboration between libraries, halal certification bodies, and academics is key in strengthening a more transparent and reliable halal information ecosystem. Some of the main challenges identified include the lack of metadata standards for halal information, limited access to primary sources, and low literacy of halal information in the community. Therefore, a strategy is needed that involves the development of an information system based on Islamic Information Science and continuous education for stakeholders. Keywords: Library; Halal Knowledge Management; Islamic Information Science; Halal Information; Halal Industry. Abstrak: Perkembangan industri halal telah menjadi fenomena global yang mencakup berbagai sektor, termasuk makanan, farmasi, kosmetik, dan keuangan. Namun, keterbatasan akses terhadap informasi halal yang valid masih menjadi tantangan utama bagi konsumen, pelaku usaha, dan peneliti. Artikel ini bertujuan untuk mengeksplorasi peran perpustakaan dalam pengelolaan pengetahuan halal (Halal Knowledge Management) serta bagaimana perpustakaan dapat menjadi pusat informasi yang kredibel dalam mendukung industri halal. Metode yang digunakan dalam penelitian ini adalah tinjauan literatur (literature review) yang merujuk pada berbagai sumber akademik terkait halal dan manajemen informasi. Hasil kajian menunjukkan bahwa perpustakaan memiliki peran strategis dalam menyediakan akses ke literatur halal, mengembangkan sistem repositori digital, serta mengintegrasikan teknologi informasi seperti blockchain dan kecerdasan buatan (AI) untuk meningkatkan validasi dan klasifikasi informasi halal. Selain itu, kolaborasi antara perpustakaan, lembaga sertifikasi halal, dan akademisi menjadi kunci dalam memperkuat ekosistem informasi halal yang lebih transparan dan terpercaya. Beberapa tantangan utama yang diidentifikasi mencakup kurangnya standar metadata untuk informasi halal, keterbatasan akses terhadap sumber primer, serta rendahnya literasi informasi halal di masyarakat. Oleh karena itu, diperlukan strategi yang melibatkan pengembangan sistem informasi berbasis Islamic Information Science serta edukasi berkelanjutan bagi pemangku kepentingan. Kata Kunci: Perpustakaan; Manajemen Pengetahuan Halal; Islamic Information Science; Informasi Halal; Industri Halal